Chemical kinetic analysis to study the potential of fuel staging in reducing the emissions from NH3/CH4-air combustion at different pressures. (1st May 2023) - Vijrumbana, Y.; Shankar Singh, Anand; Jik Lee, Bok; Mahendra Reddy, V.
Highlights: Effect of fuel staging on NOx emissions form NH3 /CH4 -air combustion is studied. The chemical kinetic analysis is performed for pressures of 1.0 & 10 atm. Fuel staging reduces the CO, NOx, and unburnt NH3 emissions at 1.0 atm. Fuel staging can be considered as an alternative approach for emissions reduction. Abstract: The combustion characteristics of ammonia/methane blends to enhance the reactivity of ammonia are investigated successfully for carbon–neutral energy applications. However, commercializing ammonia blends demands techniques to retrench the superfluous NOX emissions under fuel-lean conditions. The present study is a chemical kinetic analysis investigating a new ammonia-methane combustion strategy of injecting ammonia into hot methane combustion gases (ammonia fuel staging) to reduce the NOX propensity without ammonia slip. The combustion kinetics of NH3 /CH4 mixtures are studied in chemical reactor networks (CRNs), depicting typical burner flow conditions with and without fuel staging. A comparison of the emission chemistry in the fuel-staged CRN model with the single-stage CRN model is carried out for the ammonia mole fraction ( X NH 3 ) in the fuel mixture ranging from 20 to 60 % and the equivalence ratio ranges ( ϕ ) of 0.6–0.9 at both low and high-pressures of 1 and 10 atm, respectively. It is observed that in the single-stage reactor, the entire reactor is an active reaction zone due to the reduced chemical kinetics of methane in the presence of ammonia. Recognizing the need of raising the radical concentration and temperature in the flame zone to enhance ammonia chemistry, a fuel-staged reactor model is proposed. In the fuel-staged model, staged combustion is achieved by injecting NH3 into the lean methane combustion products for the constant combustor power output of 25 kW. Results show that fuel staging enhances the ammonia chemistry at low and high-pressure conditions of 1 and 10 atm. In the fuel-staged reactor, the flame zone of the second stage is observed to be the active reaction zone with maximum NH3 consumption. At low-pressure conditions, fuel staging leads to a reduction in both CO and NOX emissions without ammonia slip. The NOX reduction is due to the stable availability of NO-consuming NHi radicals for the entire duration of combustion in the flame zone via the reactions: 2 N H 2 → N H 3 + N H and N H 3 + O H → N H 2 + H 2 O . The CO-consuming reactions: N H 2 + C O → H N C O + H and O H + C O → H + C O 2 further reduces the CO emissions from the second stage. However, the augment in ammonia chemistry adversely affected NOX reduction at high-pressure operating conditions due to the lack of NHi radicals for NO consumption. The study contributed to the NOX reduction from ammonia combustion by providing an active high-temperature combustion zone with a self-sustaining NHi environment.